SiC particle reinforced aluminum-based composite material, preparation method and application

By adding Si, Mg and Ti to the aluminum alloy matrix and reacting with SiC particles to form SiC particle-enhanced aluminum-based composite materials, the existing problems of high brake disc density, poor thermal conductivity and poor thermal fading performance are solved, and the lightweight and multiple performance improvement of the material are achieved.

CN119843112APending Publication Date: 2025-04-18ZHENJIANG RUILONG ADVANCED MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510126256.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing brake disc has high density, poor thermal conductivity and poor thermal fading performance, making it difficult to meet the needs of modern transportation tools for lightweight, energy conservation and emission reduction.

Method used

SiC particles are used to reinforce the aluminum-based composite material, and by adding Si, Mg and Ti to the aluminum alloy matrix and reacting with SiC particles to form a material with excellent thermal conductivity, wear resistance and thermal decay properties.

Benefits of technology

It realizes lightweight material, improves thermal conductivity, wear resistance and thermal fading performance, and meets the multiple performance requirements of modern transportation vehicles for brake discs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843112A_ABST
    Figure CN119843112A_ABST
Patent Text Reader

Abstract

The invention discloses a SiC particle reinforced aluminum-based composite material, a preparation method and application, and the SiC particle reinforced aluminum-based composite material comprises the following components in percentage by mass: 6.0-11.0% of Si contained in a matrix; 0.4 to 1.1 percent of Mg; less than or equal to 0.40% of Fe; 0.30% or less of Cu; 0.20% or less of Ti; silicon carbide < = 25%; and the balance of aluminum and inevitable impurities. Silicon (Si), magnesium (Mg) and titanium (Ti) are introduced into the silicon carbide (SiC) particle reinforced aluminum-based composite material, the performance of an aluminum alloy matrix is affected, and the performance, especially the heat conduction performance, the wear resistance and the heat fading performance, of the composite material is improved through interaction of the silicon (Si), the magnesium (Mg) and the titanium (Ti) and the SiC particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a SiC particle reinforced aluminum-based composite material, a preparation method and an application thereof. Background Art

[0002] With the development of social economy and the enhancement of people's environmental awareness, higher and higher requirements are put forward for energy conservation and emission reduction of rail transit and passenger cars, and the trend of lightweight vehicles is unstoppable. Traditional rail transit and automobile brake discs are mostly cast iron and cast steel brake discs. Cast iron and cast steel brake discs have the advantages of easy processing, good wear resistance, and easy processing; however, their disadvantages are also prominent, such as: large mass, high-speed braking thermal decay, poor thermal conductivity of cast steel, easy rust on the disc surface and short life.

[0003] Currently, the wear resistance, heat dissipation capacity and thermal decay of traditional light alloys cannot meet the needs of brake discs, while carbon fiber materials and powder metallurgy materials are difficult to use in large quantities due to issues such as economy and mass production.

[0004] Therefore, the market is in urgent need of a lightweight material that can be adapted to mass production and is inexpensive to replace cast iron and cast steel brake discs to achieve the goal of energy conservation and emission reduction. In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a SiC particle reinforced aluminum-based composite material, a preparation method and an application thereof, so as to overcome the problems of the existing brake disc having high density, poor thermal conductivity and poor thermal decay performance.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a SiC particle reinforced aluminum matrix composite material, comprising the following components by mass fraction:

[0008] The Si content in the matrix is ​​6.0-11.0%;

[0009] Mg 0.4~1.1%;

[0010] Fe≤0.40%;

[0011] Cu≤0.30%;

[0012] Ti≤0.20%;

[0013] Silicon carbide ≤40%;

[0014] The balance is aluminum and unavoidable impurities.

[0015] In an optional embodiment, the following components are included by mass fraction:

[0016] Si 7.5~10.0%;

[0017] Mg 0.40~0.85%;

[0018] Fe≤0.25%;

[0019] Cu≤0.20%;

[0020] Ti 0.10%~0.20%;

[0021] Silicon carbide 18% to 22%;

[0022] The balance is aluminum and unavoidable impurities.

[0023] In an optional embodiment, it includes a SiC reinforcement phase and a eutectic silicon phase, and the eutectic silicon phase is rod-shaped and dot-shaped;

[0024] And / or, in the SiC particle reinforced aluminum-based composite material, the mass fraction of any one impurity element is ≤0.03%, and the total mass fraction of impurities is ≤0.10%.

[0025] In an optional embodiment, the SiC particle reinforced aluminum-based composite material has a cast tensile strength of ≥140 MPa;

[0026] And / or, the SiC particle reinforced aluminum-based composite material has a cast yield strength of ≥115 MPa;

[0027] And / or, the SiC particle reinforced aluminum-based composite material has a cast hardness of ≥65HB;

[0028] And / or, the cast elongation of the SiC particle reinforced aluminum-based composite material is ≥0.5%;

[0029] And / or, the cast thermal conductivity of the SiC particle reinforced aluminum-based composite material is ≥150 W / (m*K);

[0030] And / or, the cast thermal diffusion coefficient of the SiC particle reinforced aluminum-based composite material is ≥70 mm 2 / s;

[0031] And / or, the cast friction coefficient of the SiC particle reinforced aluminum-based composite material is ≥0.3;

[0032] And / or, the SiC particle reinforced aluminum-based composite material has a casting density of 2.7 to 2.8 g / cm 3 .

[0033] In a second aspect, the present invention provides a method for preparing the SiC particle reinforced aluminum-based composite material according to any one of the aforementioned embodiments, comprising:

[0034] Weighing raw materials according to mass ratio, and melting the raw materials to obtain a melt;

[0035] The activated silicon carbide particles are added to the melt to carry out a composite reaction, so as to obtain the SiC particle reinforced aluminum-based composite material.

[0036] In an optional embodiment, the temperature of the composite reaction step is 570° C. to 730° C., and the time is 30 min to 120 min.

[0037] In an optional embodiment, the method for activating the silicon carbide particles comprises: keeping the silicon carbide particles warm under aerobic conditions for 5 hours to 24 hours at a temperature of 900° C. to 1600° C.

[0038] In an optional embodiment, the particle size of the silicon carbide particles is 3 to 50 μm.

[0039] In an optional embodiment, the purity of the silicon carbide particles is ≥ 90%.

[0040] And / or, the mass fraction of free iron in the silicon carbide particles is ≤0.2%.

[0041] In a third aspect, the present invention provides a brake disc made of the SiC particle reinforced aluminum-based composite material described in any one of the aforementioned embodiments.

[0042] The present invention has the following beneficial effects:

[0043] Silicon (Si), magnesium (Mg) and titanium (Ti) are introduced into the silicon carbide (SiC) particle reinforced aluminum-based composite material of the present application, which not only affects the performance of the aluminum alloy matrix itself, but also improves the performance of the composite material by interacting with the SiC particles, especially the thermal conductivity, wear resistance and thermal decay performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0045] Figure 1 This is the metallographic image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Example 1.

[0046] Figure 2 This is a photo of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Comparative Example 1.

[0047] Figure 3 This is the metallographic image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Comparative Example 3.

[0048] Figure 4 This is the flaw detection image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Comparative Example 3.

[0049] Figure 5 This is the metallographic image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Comparative Example 5.

[0050] Figure 6 This is the metallographic image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Comparative Example 6. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0052] The embodiment of the present invention provides a SiC particle reinforced aluminum-based composite material, which includes the following components by mass fraction:

[0053] The Si content in the matrix is ​​6.0-11.0%;

[0054] Mg 0.4~1.1%;

[0055] Fe≤0.40%;

[0056] Cu≤0.30%;

[0057] Ti≤0.20%;

[0058] Silicon carbide ≤40%;

[0059] The balance is aluminum and unavoidable impurities.

[0060] In silicon carbide (SiC) particle reinforced aluminum matrix composites, silicon (Si), magnesium (Mg) and titanium (Ti) not only affect the properties of the aluminum alloy matrix itself, but also improve the properties of the composites by interacting with SiC particles, especially the thermal conductivity, wear resistance and thermal decay properties.

[0061] Specifically, the Si content in the matrix is ​​6.0-11.0%, for example, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, etc. Silicon can form a solid solution in the matrix, improve the strength and hardness of the material, and reduce defects such as shrinkage cavities and pores; the mass fraction of Mg in the SiC particle reinforced aluminum-based composite material is 0.4-1.1%, for example, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, etc. Magnesium mainly improves the strength of the aluminum alloy through two mechanisms: solid solution strengthening and aging precipitation strengthening, and can inhibit the formation of coarse eutectics, which is beneficial to the uniformity and density of the microstructure. In addition, Mg can also react with the film formed on the surface of the activated silicon carbide particles. , forming MgO, which is also beneficial to enhancing the bonding force between silicon carbide particles and the matrix; the mass fraction of Ti in the SiC particle reinforced aluminum-based composite material is less than 0.20%, for example, it can be 0.2%, 0.19%, 0.18%, 0.17%, 0.16%, 0.15%, 0.14%, 0.13%, 0.12%, 0.11%, 0.10%, 0.05%, etc., adding a small amount of Ti during the smelting process of aluminum alloy can significantly refine the grain size, and can also play a strengthening role, and also help to maintain the stability of the material at high temperature, further, it can also react with the film layer formed on the surface of the activated silicon carbide particles to form Ti-Si, which is also beneficial to enhancing the bonding force between the silicon carbide particles and the matrix.

[0062] It should be noted that the silicon in the SiC particle reinforced aluminum-based composite material of the present application is divided into two parts, the silicon in the silicon carbide reinforced particles and other silicon elements. In the present application, taking the mass of the SiC particle reinforced aluminum-based composite material as 100%, the mass fraction of Si contained in the matrix is ​​6.0-11.0%, which refers to the silicon in the SiC particle reinforced aluminum-based composite material excluding silicon carbide particles.

[0063] In an optional embodiment, the following components are included by mass fraction:

[0064] The Si content in the matrix is ​​7.5-10.0%;

[0065] Mg 0.40~0.85%;

[0066] Fe≤0.25%;

[0067] Cu≤0.20%;

[0068] Ti 0.10%~0.20%;

[0069] Silicon carbide 18% to 22%;

[0070] The balance is aluminum and unavoidable impurities.

[0071] Further optimization of the dosage of each component will help to further improve the performance of SiC particle reinforced aluminum-based composites.

[0072] In an optional embodiment, it includes a SiC reinforcement phase and a eutectic silicon phase, and the eutectic silicon phase is rod-shaped and dot-shaped;

[0073] The rod-shaped eutectic silicon phase in silicon carbide reinforced aluminum alloy can provide macroscopic strengthening effect and wear resistance, and can enhance the thermal conductivity of the composite material. The point-shaped eutectic silicon phase in silicon carbide reinforced aluminum alloy can refine the structure at the microscopic level and improve the plastic deformation ability and fatigue resistance. Reasonable regulation of the rod-shaped and point-shaped eutectic silicon phases can improve the toughness of the material while maintaining high strength, and also improve properties such as wear resistance and thermal conductivity.

[0074] And / or, in the SiC particle reinforced aluminum-based composite material, the mass fraction of any one impurity element is ≤0.03%, and the total mass fraction of impurities is ≤0.10%.

[0075] In an optional embodiment, the SiC particle reinforced aluminum-based composite material has a cast tensile strength of ≥140 MPa;

[0076] And / or, the SiC particle reinforced aluminum-based composite material has a cast yield strength of ≥115 MPa;

[0077] And / or, the SiC particle reinforced aluminum-based composite material has a cast hardness of ≥65HB;

[0078] And / or, the cast elongation of the SiC particle reinforced aluminum-based composite material is ≥0.5%;

[0079] And / or, the cast thermal conductivity of the SiC particle reinforced aluminum-based composite material is ≥150 W / (m*K);

[0080] And / or, the cast thermal diffusion coefficient of the SiC particle reinforced aluminum-based composite material is ≥70 mm 2 / s;

[0081] And / or, the cast friction coefficient of the SiC particle reinforced aluminum-based composite material is ≥0.3;

[0082] And / or, the SiC particle reinforced aluminum-based composite material has a casting density of 2.7 to 2.8 g / cm 3 .

[0083] The performance of the SiC particle reinforced aluminum-based composite material prepared by the embodiments of the present application can meet the above requirements and has advantages over existing cast iron, cast steel and existing aluminum alloy materials.

[0084] An embodiment of the present invention further provides a method for preparing the SiC particle reinforced aluminum-based composite material according to any one of the aforementioned embodiments, comprising:

[0085] Weighing raw materials according to mass ratio, and melting the raw materials to obtain a melt;

[0086] The activated silicon carbide particles are added to the melt to carry out a composite reaction, so as to obtain the SiC particle reinforced aluminum-based composite material.

[0087] In the existing silicon carbide particle reinforced materials, the bonding force between the silicon carbide particles and the matrix is ​​relatively small and they are easy to fall off. Therefore, in the present application, activated silicon carbide particles are added to the aluminum alloy melt. After the silicon carbide particles are activated, their surfaces can react with the aluminum alloy melt, so that chemical bonds are formed between silicon and aluminum or other elements in the aluminum alloy melt, which is beneficial to improve the bonding force between the silicon carbide particles and the matrix.

[0088] In addition, the raw material in the present application may include an aluminum alloy ingot, and a master alloy is added to the aluminum alloy ingot to increase the content of silicon, magnesium and titanium in the raw material, so as to improve the bonding force between the silicon carbide particles and the matrix while maintaining the composite material with better comprehensive properties. In some embodiments, the grade of the aluminum alloy ingot may be AlSi7Mg, AlSi9Mg, Al Si9Cu3, etc.

[0089] In an optional embodiment, the temperature of the composite reaction step is 570°C to 730°C, specifically 570°C, 580°C, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 730°C or any value between 570°C and 730°C, and the time is 30min to 120min, specifically 30min, 60min, 90min, 120min or any value between 30min and 120min.

[0090] In some embodiments, the composite reaction step can be accompanied by stirring, and the stirring speed is ≥300r / min; the activated silicon carbide particles can be added slowly, for example, the addition rate is ≤4kg / min, specifically it can be 4kg / min, 3kg / min, 2kg / min, 1kg / min, 0.5kg / min or any value less than 4kg / min. The lower the addition rate, the more conducive to the uniform dispersion of the activated silicon carbide particles. However, too low an addition rate will lead to a decrease in production efficiency. Therefore, in some embodiments, the addition rate of the activated silicon carbide particles can be 1kg / min-4kg / min, and the activated silicon carbide particles can be added in a continuous or intermittent manner. The composite reaction can be carried out under vacuum conditions, and the vacuum degree of the vacuum conditions is ≤100Pa, which is conducive to reducing the entry of gas.

[0091] In an optional embodiment, the method for activating the silicon carbide particles comprises: keeping the silicon carbide particles warm under aerobic conditions for 5 hours to 24 hours at a temperature of 900° C. to 1600° C.

[0092] Among them, the insulation temperature can be 900℃~1600℃, specifically 900℃, 1000℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃ or any value between 900℃ and 1600℃; the insulation time can be 5h, 9h, 13h, 17h, 20h, 24h or any value between 5h and 24h.

[0093] Under the above conditions, the silicon carbide particles can be fully activated. It should be noted that the silicon carbide particles can be stirred or turned during the activation process to facilitate full and uniform activation of the silicon carbide particles while avoiding adhesion between the particles.

[0094] In an optional embodiment, the particle size of the silicon carbide particles is 3 to 50 μm.

[0095] The smaller the particle size of silicon carbide particles, the better their uniform dispersion in the melt. However, if the particles are too small, the fluidity of the melt will be reduced, which is not conducive to subsequent production. Therefore, the particle size of silicon carbide particles should be maintained between 3 and 50 μm.

[0096] In an optional embodiment, the purity of the silicon carbide particles is ≥ 90%.

[0097] And / or, the mass fraction of free iron in the silicon carbide particles is ≤0.2%.

[0098] Selecting silicon carbide particles with higher purity can reduce the introduction of impurities. Since free iron has more opportunities to be introduced and is easier to enter the composite material than other elements, it needs to be focused on control.

[0099] An embodiment of the present invention further provides a brake disc, the material of which is the SiC particle reinforced aluminum-based composite material described in any one of the aforementioned embodiments.

[0100] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0101] Example 1

[0102] This embodiment provides a method for preparing a SiC particle reinforced aluminum-based composite material, which specifically comprises the following steps:

[0103] Step 1, keeping silicon carbide particles warm for 5 hours under aerobic conditions at a temperature of 1600° C. to obtain activated silicon carbide particles, wherein the silicon carbide particles have a particle size of 3 to 50 μm, a purity of 99%, and a mass fraction of free iron ≤0.2%.

[0104] Step 2, melting the AlSi9Mg matrix and refining and degassing it, adding pure magnesium and AlTi5B1 to adjust the composition of the melt to obtain an aluminum alloy melt;

[0105] Step 3, adding activated SiC particles to the aluminum alloy melt and performing sufficient stirring and composite reaction at the same time, the composite reaction temperature is 610° C., the time is 120 min, and the surface scum is cleaned after the composite reaction to obtain a SiC particle reinforced aluminum-based composite material, wherein the SiC particle reinforced aluminum-based composite material includes, by mass fraction, 10.0% Si, 0.67% Mg, 0.18% Fe, 0.11% Ti, 20% silicon carbide, and a very small amount of B contained in the matrix.

[0106] Example 2

[0107] This embodiment provides a method for preparing a SiC particle reinforced aluminum-based composite material, which specifically comprises the following steps:

[0108] Step 1, keeping the silicon carbide particles warm for 24 hours under aerobic conditions at a temperature of 1050° C. to obtain activated silicon carbide particles, wherein the silicon carbide particles have a particle size of 3 to 50 μm, a purity of ≥99%, and a mass fraction of free iron of ≤0.2%.

[0109] Step 2, melting the AlSi9Cu3 aluminum alloy matrix and refining and degassing it, adding pure magnesium and AlTi5B1 master alloy to adjust the composition of the melt to obtain an aluminum alloy melt;

[0110] Step 3, adding activated SiC particles to the aluminum alloy melt and performing sufficient stirring and composite reaction at the same time, the composite reaction temperature is 660°C, the time is 90 minutes, and the surface scum is cleaned after the composite reaction to obtain a SiC particle reinforced aluminum-based composite material, wherein the SiC particle reinforced aluminum-based composite material includes, by mass fraction, 9.5% Si, 0.6% Mg, 0.25% Fe, 0.20% Cu, 0.128% Ti, and 25% silicon carbide contained in the matrix.

[0111] Example 3

[0112] This embodiment provides a method for preparing a SiC particle reinforced aluminum-based composite material, which specifically comprises the following steps:

[0113] Step 1, keeping the silicon carbide particles warm for 6 hours under aerobic conditions at a temperature of 1300° C. to obtain activated silicon carbide particles, wherein the silicon carbide particles have a particle size of 3 to 50 μm, a purity of ≥90%, and a mass fraction of free iron of ≤0.2%.

[0114] Step 2, melting the AlSi9Mg matrix and performing a refining and degassing treatment, adding pure magnesium and AlTi5B1 master alloy to adjust the composition of the melt, and obtaining an aluminum alloy melt;

[0115] Step 3, adding activated SiC particles to the aluminum alloy melt and performing sufficient stirring and composite reaction at the same time, the composite reaction temperature is 650°C, the time is 100 minutes, and the surface scum is cleaned after the composite reaction to obtain a SiC particle reinforced aluminum-based composite material, wherein the SiC particle reinforced aluminum-based composite material includes, by mass fraction: Si 10.8%, Mg 0.85%, Fe 0.30% (derived from impurities in the equipment or each component), Cu 0.18%, Ti 0.14%, and silicon carbide 10% contained in the matrix.

[0116] Comparative Example 1

[0117] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that no intermediate alloy and pure magnesium are added in step 2, and activated SiC particles are directly added to the aluminum alloy matrix melt in step 3. The mass fractions of silicon, magnesium and titanium in the prepared SiC particle reinforced aluminum-based composite material are reduced, specifically, by mass fraction, including: 10.0% Si, 0.30% Mg, 0.18% Fe, 0.02% Ti, and 20% silicon carbide contained in the matrix.

[0118] Comparative Example 2

[0119] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that the SiC is not activated.

[0120] Comparative Example 3

[0121] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that pure magnesium is added in step 2 instead of silicon, and the prepared SiC particle reinforced aluminum-based composite material includes, by mass fraction, 11.3% Si, 0.31% Mg, 0.19% Fe, 0.11% Ti, and 20% silicon carbide contained in the matrix.

[0122] Comparative Example 4

[0123] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that in step 1, the silicon carbide particles are heated to 800° C. in air and kept warm.

[0124] Comparative example: 5

[0125] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that the insulation time in step 1 is 3 hours.

[0126] Comparative Example 6

[0127] This comparative example provides a method for preparing a SiC particle reinforced aluminum-based composite material, which is different from Example 1 mainly in that the composite reaction temperature in step 3 is 560°C.

[0128] The above embodiments are put into practical operation, and the test results are as follows:

[0129] The metallographic image of the silicon carbide particle reinforced aluminum-based composite ingot sample corresponding to Example 1 is as follows: Figure 1 As shown, Figure 1 In the figure, the dark gray particles are SiC reinforcement phase, the light gray slender rods and dots are eutectic silicon, and the white part is the matrix.

[0130] Comparative Example 1: The obtained aluminum ceramic melt has very poor fluidity and cannot be put into production of castings. The prepared casting sample photo is shown in Figure 2 As shown;

[0131] Comparative Example 2: SIC particles were added to the aluminum matrix as described above, but the batching failed;

[0132] Comparative Example 3: The obtained aluminum ceramic melt has poor fluidity, poor dispersion of SIC particles, agglomeration, low qualified rate of castings put into production, and easy to produce porosity defects. The metallographic diagram of the prepared casting is as follows Figure 3 As shown, the flaw detection diagram is as follows Figure 4 As shown;

[0133] Comparative Example 4: The SIC particles could not be activated and could not be combined with the aluminum matrix, and the batching failed;

[0134] Comparative Example 5: SIC activation is insufficient, a large amount of gas is released during the batching process, the porosity of the aluminum ceramic melt exceeds the standard, the SIC particles are seriously agglomerated, the material is unqualified, and the metallographic image of the prepared casting is as follows: Figure 5 shown.

[0135] Comparative Example 6: The aluminum liquid temperature is too low, the aluminum liquid has too much solid phase, the stirring resistance is extremely large, the stirring speed cannot be increased (the stirring rod will be damaged if the stirring resistance is too large at a high speed), the SIC cannot be evenly distributed, the agglomeration is serious, and the metallographic diagram of the prepared casting is as follows Figure 6 shown.

[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A SiC particle reinforced aluminum matrix composite material, characterized in that: The components by mass fraction are as follows: The Si content in the matrix is ​​6.0-11.0%; Mg 0.4~1.1%; Fe≤0.40%; Cu≤0.30%; Ti≤0.20%; Silicon carbide ≤40%; The balance is aluminum and inevitable impurities.

2. The SiC particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The components by mass fraction are as follows: The Si content in the matrix is ​​7.5-10.0%; Mg 0.40~0.85%; Fe≤0.25%; Cu≤0.20%; Ti 0.10%~0.20%; Silicon carbide 18% to 22%; The balance is aluminum and inevitable impurities.

3. The SiC particle reinforced aluminum matrix composite material according to claim 1, characterized in that: It includes a SiC reinforcement phase and a eutectic silicon phase, wherein the eutectic silicon phase is rod-shaped and dot-shaped; And / or, in the SiC particle reinforced aluminum-based composite material, the mass fraction of any one impurity element is ≤0.03%, and the total mass fraction of impurities is ≤0.10%.

4. The SiC particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The as-cast tensile strength of the SiC particle reinforced aluminum-based composite material is ≥140MPa; And / or, the SiC particle reinforced aluminum-based composite material has a cast yield strength of ≥115 MPa; And / or, the SiC particle reinforced aluminum-based composite material has a cast hardness of ≥65HB; And / or, the cast elongation of the SiC particle reinforced aluminum-based composite material is ≥0.5%; And / or, the cast thermal conductivity of the SiC particle reinforced aluminum-based composite material is ≥150 W / (m*K); And / or, the cast thermal diffusion coefficient of the SiC particle reinforced aluminum-based composite material is ≥70 mm 2 / s; And / or, the cast friction coefficient of the SiC particle reinforced aluminum-based composite material is ≥0.3; And / or, the SiC particle reinforced aluminum-based composite material has a casting density of 2.7 to 2.8 g / cm 3 .

5. A method for preparing the SiC particle reinforced aluminum-based composite material according to any one of claims 1 to 4, characterized in that: include: Weighing raw materials according to mass ratio, and melting the raw materials to obtain a melt; The activated silicon carbide particles are added to the melt to carry out a composite reaction, so as to obtain the SiC particle reinforced aluminum-based composite material.

6. The method for preparing the SiC particle reinforced aluminum-based composite material according to claim 5, characterized in that: The temperature of the composite reaction step is 570° C. to 730° C., and the time is 30 min to 120 min.

7. The method for preparing the SiC particle reinforced aluminum-based composite material according to claim 5, characterized in that: The activation method of the silicon carbide particles comprises: keeping the silicon carbide particles warm under aerobic conditions for 5 hours to 24 hours at a temperature of 900° C. to 1600° C.

8. The method for preparing the SiC particle reinforced aluminum-based composite material according to claim 5, characterized in that: The particle size of the silicon carbide particles is 3 to 50 μm.

9. The method for preparing the SiC particle reinforced aluminum-based composite material according to claim 5, characterized in that: The purity of the silicon carbide particles is ≥90%; And / or, the mass fraction of free iron in the silicon carbide particles is ≤0.2%.

10. A brake disc, characterized in that: The material is the SiC particle reinforced aluminum-based composite material as described in any one of claims 1-4.